Assessing the Influence of Responsive Disorder on the Academic Performance of Married Post-graduate Students in North eastern Universities in Nigeria - Christian Igomu , Amuche; Naomi Nuhu, Adamu (International Journal of Scientific Research and Management (IJSRM), 2019)
The study assessed the influence of Responsive disorder on the academic performance of married post-graduate students in North Eastern Universities in Nigeria. Two research questions and two null hypotheses were formulated in harmony with the objectives of the study. The design of this study is survey. The population of the study consist of 22,772 married post-graduate students from 4 Universities in North-east, Nigeria. The sample size for the study was 422 determined using the Proportionate sampling strategy employed at different levels in selection of postgraduate students from the four Universities and along gender lines. The researcher developed two instruments for data collection for the study titled: Students’ Responsive disorder Inventory and Research and Statistics Achievement Test. The reliabilities of the instruments yielded 0.84 and 0.87 reliability coefficients of internal consistency for SRDI and RSAT respectively. Descriptive statistics were used to summarize data related to the research questions. Linear regression statistic was used to test the formulated null hypotheses. It was found that postgraduate students face Responsive disorder even with an above average level academic performance. However, Responsive disorder significantly influenced academic achievement of postgraduate students who are married in Universities in North-east Nigeria. Also, Responsive disorder significantly predicts academic achievement of postgraduate students irrespective of gender. The study concludes that there is relatively high level agreement among postgraduate students in the North-east states with respect to the Responsive disorder faced by them. The finding debunks traditional beliefs that married people are more likely to perform poorly or even drop-out. This study found support for the position that married people may beat the single and even complete their studies before the singles. The study recommends among others that; coping strategies be evolved to help resolve the debacle; Scholarships should be awarded to students to reduce the financial burden, and, efforts should be invested in promoting emotional health among post-graduate students in order to mellow the negative effect on their academic performance.